A case series of vital signs‐controlled, patient‐assisted intravenous analgesia (VPIA) using remifentanil for labour and delivery - Leong, W. L.; Sng, B. L.; Zhang, Q.; Han, N. L. R.; Sultana, R.; Sia, A. T. H. (Anaesthesia, 2017)
Summary Intravenous remifentanil patient‐controlled analgesia can be used during labour as an alternative to epidural analgesia. Adverse effects of opioids, including hypoxia and bradycardia, may lead to maternal morbidity and mortality. We devised an interactive feedback system based on a clinical proportional algorithm, to continuously monitor for adverse effects to enhance safety and better titrate analgesia. This vital signs‐controlled, patient‐assisted intravenous analgesia with remifentanil used a prototype delivery system linked to a pulse oximeter that evaluated maternal oxygen saturation and heart rate continuously. With this system, we detected oxygen saturation < 95% for more than 60 s in 15 of 29 subjects (52%); and heart rate < 60 min−1 for more than 60 s in 7 of 29 subjects (24%) during use. The system automatically responded appropriately by reducing the dosages and temporarily halting remifentanil administration, thus averting further hypoxia and bradycardia.